Impaired platelet‐dependent thrombin generation associated with thrombocytopenia is improved by prothrombin complex concentrates in vitro. Issue 2 (14th February 2020) - Chowdary, Pratima; Hamid, Colleen; Slatter, David; Morris, Richard; Foley, Jonathan H.; Gomez, Keith; Brodkin, Edgar; Fox, Thomas A.; Gatt, Alex; McVey, John H.
Abstract: Background: Impaired thrombin generation (TG) in patients with acquired coagulopathy, is due to low coagulation factors and thrombocytopenia. The latter is typically treated with platelet transfusions and the former with plasma and occasionally with prothrombin complex concentrates (PCCs). We hypothesized that manipulating the concentrations of coagulation factors might result in restoration of platelet‐dependent TG over and above that of simple replacement therapy. Objective: To investigate the influence of PCCs on impaired TG secondary to thrombocytopenia. Methods: TG was evaluated by thrombin generation assay using a thrombocytopenia model in which normal plasma samples with varying platelet counts (20‐300 × 10 9 /L) were spiked with PCCs (25%‐150% increase in plasma PCC levels). Results: PCCs and platelets significantly increased TG in a dose‐dependent manner in vitro. Two‐way repeated measures of analysis of variance showed variance in peak height, area under the curve, time to peak, and velocity. This variance explained, respectively, by levels of PCC was 47, 59, 25 and 53%; by platelet count was 45, 28, 44, and 14%; by the combination was 80, 67, 70, and 62% variance; and a combination with additional interaction was 91, 84, 76, and 68%. TG at a platelet count 40 × 10 9 /L with an approximate 25% increase in PCC concentration was similar to TG at 150 × 10 9 /L. Similarly, patient samples spiked ex vivo with PCCs also showed highly significant improvements in TG. Conclusions: Impaired TG of thrombocytopenia is improved by PCCs, supporting the need for additional studies in complex coagulopathies characterized by mild to moderate thrombocytopenia and abnormal coagulation.